Strike three - Smith, Stephen D. (Stephen Dodd), 1961-; Caldwell, Lise, 1974- (Cincinnati, Ohio : Standard Pub., 2006)
As she is getting ready to graduate from eighth grade, Stephanie relies on God's help when she joins a softball team with some angry teammates, makes a new friend who is struggling with anorexia, and tries to figure out her changing relationship with the boy who has been her best friend since grade school.
5.2
3-6
3-6
Keywords: Christian life -- Juvenile fiction; Softball -- Juvenile fiction; Anorexia nervosa -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Competition (Psychology) -- Juvenile fiction; People with disabilities -- Juvenile fiction; Christian life -- Fiction; Softball -- Fiction; Anorexia nervosa -- Fiction; Interpersonal relations -- Fiction; Competition (Psychology) -- Fiction; People with disabilities -- Fiction; Christian life -- Fiction; Softball -- Fiction; Anorexia nervosa -- Fiction; Interpersonal relations -- Fiction; Competition -- Fiction; Handicapped -- Fiction